Balancing responsibilities, rewards and challenges: A qualitative study illuminating the complexity of being a rapid response team nurse. Issue 23 (5th January 2022) - Bunkenborg, Gitte; Barfod O'Connell, Malene; Jensen, Hanne Irene; Bucknall, Tracey
Abstract: Aim and Objective: To explore Rapid Response Team nurses' perceptions of what it means being a Rapid Response Team nurse including their perceptions of the collaborative and organisational aspects of the rapid response team (RRT). Background: For more than 20 years, RRT nurses have been on the frontline of critical situations in acute care hospitals. However, a few studies report nurses' perceptions of their role as RRT nurses, including collaboration with general ward nurses and physicians. This knowledge is important to guide development and adjustment of the RRT to benefit both patients' safety and team members' job satisfaction. Design: Qualitative focus group interviews. Methods: A qualitative approach was applied. Throughout 2018 and across three regions and three acute care settings in Denmark, eight focus group interviews were conducted in which 27 RRT nurses participated. Transcribed interviews were analysed using inductive content analysis. Reporting of this study followed the COREQ checklist. Results: One overarching theme 'Balancing responsibilities, rewards, and challenges' was derived, comprising six categories: 'Becoming, developing and fulfilling the RRT nurse role', 'Helping patients as the core function of RRT', 'The RRT‐call at its best', 'The obvious and the subtle RRT tasks', 'Carrying the burden of the RRT', and 'Organisational benefits and barriers for an optimal RRT'. Conclusion: Being a RRT nurse is a complex task. Nurses experience professional satisfaction and find it meaningful helping deteriorating patients. The inadequate resources available to train general ward staff how to manage basic clinical tasks are an added stress to nurses. Relevance to clinical practice: Organisational managers need a better understanding of the necessary staffing requirements to attend patients' needs, train staff and handle the increasing acuity of ward patients. Failure to do so will be detrimental to patient outcomes and compromise RRT nurses' job satisfaction.